Phenotypic appearance the yield character of five genotypes of cayenne pepper at Sukamantri, Ciamis - Eva Oktaviani; Neni Rostini; Agung Karuniawan (Zuriat, 2018)
The purpose of this experiment is to evaluate the phenotypic appearance the yield character of five genotypes of cayenne pepper at Sukamantri, Ciamis region. The experiment used a randomized block design, with five replications. The experiment material consists of five genotypes of cayenne pepper, namely Unpad Ratuni, CR8873, Dewata, Taruna, and Rabani. The experiment was conducted at Sukamantri, Ciamis with altitude of 983 m above sea level (asl.) from August 2017 to February 2018. Data observed included fruit length, fruit diameter, fruit weight per fruit, fruit weight per plant, fruit weight per plot, and fruit weight per hectare. The experiment results show that there are differences in phenotypic characters among the five genotypes tested. Genotypes of the Gods, CR8873, and Ratuni Unpad show the highest potential yield (10.961 ton/ha, 0.345, and 10.232), with fruit weight of fruit per 1.382 gram, 0.911 grams, and 1.311 grams.Keywords: cayenne pepper, phenotypic character, yield